"Design and Molecular Docking of a Fusion Protein Targeting SARS-CoV-2 Spike Cleavage Sites" - Mohan Kumar B S,; Sethupathi Raj S,; Kumar,; Shalini K S,; V. N. Narasimha Murthy,; Rudresh Kumar KJ, (The Bioscan, 2023)
SARS-CoV-2, the virus responsible for the COVID-19 pandemic, relies on its spike protein to bind to and enter host cells. The transmembrane serine protease TMPRSS2 plays a critical role in cleaving the spike protein at specific sites, facilitating viral fusion with the host cell membrane. This study presents the computational design and molecular docking of a fusion protein, named Happy, which combines an EK1 peptide inhibitor with the C fragment of tetanus toxoid. Two variants—Happy_00 (no linker) and Happy_06 (six GGGS linkers)—were developed and evaluated for their ability to bind the spike protein cleavage sites (Arg685/Ser686 and Arg815/Ser816). Using molecular modeling tools such as RaptorX, PyMol, and Modeller, along with virtual screening via ClusPro and HADDOCK 2.4, we identified Happy_00 and Happy_06 as optimal inhibitors. Binding energies were calculated as -11.4 kcal/mol for Happy_00 at the first cleavage site and -15.4 kcal/mol for Happy_06 at the second site. The results suggest that the presence of GGGS linkers enhances flexibility, improving binding efficiency at deeper cleavage sites. Both inhibitors effectively block TMPRSS2’s cleavage activity, potentially preventing viral entry into host cells. This research highlights the promise of fusion proteins as therapeutic agents to inhibit SARS-CoV-2 infection, though further experimental validation is required to confirm in vivo efficacy.